2022
DOI: 10.3390/nu14204413
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Evaluation of Antidiabetic Properties and Mechanisms of Ficus tikoua Bur.

Abstract: In folk medicine, Ficus tikoua (F. tikoua) has been used to treat diabetes for a long time, but there is a rare modern pharmacological investigation for its antidiabetic effect and mechanisms. Our study aimed to evaluate its hypoglycemic effect using in vitro and in vivo experimental models and then explore the possible mechanisms. In the ethanol extracts and fractions of F. tikoua, n−butanol fraction (NBF) exhibited the most potent effect on inhibiting α-glucosidase activity (IC50 = 0.89 ± 0.04 μg/mL) and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, our results indicated that QG upregulated Akt phosphorylation in the presence of insulin, highlighting its potential role in activating insulin-dependent pathways ( Figure 5 ). A previous study exhibited that the ethanolic extract of Ficus tikoua improved glucose uptake through the AMPK and PI3K/Akt pathways in 3T3-L1 adipocytes and diabetic mice [ 44 ]. This finding implies that QG improves glucose absorbance in myoblasts by activating AMPK and insulin dependent Akt signaling via PTP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our results indicated that QG upregulated Akt phosphorylation in the presence of insulin, highlighting its potential role in activating insulin-dependent pathways ( Figure 5 ). A previous study exhibited that the ethanolic extract of Ficus tikoua improved glucose uptake through the AMPK and PI3K/Akt pathways in 3T3-L1 adipocytes and diabetic mice [ 44 ]. This finding implies that QG improves glucose absorbance in myoblasts by activating AMPK and insulin dependent Akt signaling via PTP inhibition.…”
Section: Discussionmentioning
confidence: 99%
“… •The upregulation of p-PI3K and p-Akt in 3T3-L1 adipocytes might mediate the possible mechanism of NBF in increasing glucose uptake. [ 282 ] 3 Ganoderma resinaceum Triterpenoid lactones α-glucosidase inhibitor An in vitro α-glucosidase inhibitory assay Compounds 1 and 2 were more potent α-glucosidase inhibitors than acarbose, with IC50 values of 0.75 ± 0.018 mM and 1.64 ± 0.022 mM, respectively. [ 44 ] 4 Cyclocarya paliurus Triterpenoid glycosides isolated from leaves ethanol extract Increase glucose uptake via AMPK/p38 pathways An in vitro study in 3T3-L1 adipocytes and C2C12 myotubes Compound 1 significantly enhanced insulin-stimulated glucose uptake in 3T3-L1 adipocytes and C2C12 myotubes.…”
Section: Introductionmentioning
confidence: 99%